Association between Serum Amiloid A (SAA) in salivary glands and high levels of circulating β2-microglobulin in patients with Sjögren syndrome - M. Benucci; F. Li Gobbi; A. Del Rosso; G. Gambacorta; A. Mannoni (Reumatismo, 2003)
Objectives: The presence of secondary amyloidosis is a complication of different rheumatic diseases. We investigated the presence of Serum Amiloid A (SAA), marker of secondary amiloidosis, in salivary glands of patients (pts) with Sjögren Syndrome (SS) and correlated it to biohumoral parameters. Materials and methods: 141 pts with sicca syndrome who fulfilled 3 items of the European Criteria for SS by Vitali et al underwent biopsies of labial salivary glands, that were scored according to Chisholm and Mason index and evaluated for the presence of SAA. All pts were evaluated for ANA, ENA, rheumatoid factor, γ-globulins, IgA, IgG, IgM, C3, C4, β2-microglobulin, erythrosedimentation rate, C reactive protein. Results: Forty out of 141 pts, showed sialoadenitis (SL) with focus score 3-4 (definite SS), and 101 pts showed SL with focus score 1-2. Fourteen out of 101 pts (13.8%) with score 1-2 and 12/40 pts (30%) with definite SS were positive for SAA, respectively. SS pts were further divided in group A (positive for SAA) and group B (negative for SAA). These groups were compared to detect if differences could exist in biohumoral parameters: group A showed higher levels of biohumoral parameters than group B, but the difference was significant only for β2-microglobulin: 2653+610 ng/ml versus 1848+440 ng/ml; p< 0.025. Conclusion: Secondary amiloydosis is a complication of SS. In pts with SAA in salivary glands were detected high levels of β2-microglobulin, that could be considered a factor predicting the development of amiloidosis in SS.